Debt covenants and accounting choice - Begley, Joy (Journal of Accounting and Economics, 1990)
In this issue Duke and Hunt and Press and Weintrop show that leverage is significantly related to the existence of, and closeness to, accounting-based debt covenants. Alternative rationales for this relation are presented. The theory requires more rigorous specification to define closeness to covenants and determine which measure of leverage produces a more appropriate proxy for closeness to covenants. Then Healy and Palepu investigate a sample of firms close to their dividend restriction and find in general they are no more likely than other firms to change accounting methods. Their sample selection criteria reduces the generalizability of their results.